Prioritățile Strategiei privind părăsirea timpurie a școlii problematizate în relație cu evoluția participării școlare în 2008–2018 - Borș, Octavia (Calitatea Vieții, 2020)
2020 is the last year of the Romanian, sectorial strategies implementation for education and training, which were designed to meet the targets set by Europe 2020. The strategy aiming to reduce early school leaving in Romania includes measures that were supposed to reduce the indicator to 11.3%, by 2020. However, in 2018, after three years after the strategy was published, the early school leaving rate decreased by only 2.7 p.p., reaching 16.4% (Eurostat, 2019). Although the progress is important, the rate is decreasing too slowly, compared to the proposed target. In preparation for the strategy’s impact studies, which should explain the rate`s slow decrease, the article aims to (a) analyze and discuss the evolution of the school participation rate and early school leaving rate during 2008–2018; (b) to analyze and discuss the importance given to family related factors in the strategy aiming to reduce early school leaving.